Female homicides in Brazil: global burden of disease study, 2000–2018Research in context - Nadia Machado de Vasconcelos; Juliana Bottoni de Souza; Adauto Martins Soares Filho; Polyanna Helena Coelho; Sofia Reinach; Caroline Stein; Crizian Saar Gomes; Luisa Sorio Flor; Emmanuela Gakidou; Antonio Luiz Pinho Ribeiro; Deborah Carvalho Malta (The Lancet Regional Health. Americas)
Summary: Background: Female homicides are a public health-relevant issue, and its spatial distribution may evidence socioeconomic vulnerabilities. This study aims to analyze the temporal and spatial trends of female homicides in Brazil and investigate socioeconomic-demographic factors associated with it. Methods: This is an ecological, descriptive, and analytical epidemiological study investigating the age-standardized female homicide rate in all Brazilian municipalities between 2000 and 2018, divided into three periods. Spatial and temporal analyses were conducted using the Global Moran's Index and LISA to identify clusters of high and low rates. Rates were also calculated by population size and means of violence across macro-regions. For the last period, a multivariable linear regression model analyzed the association of female homicide rates with social, economic, and geographic factors. Findings: Female homicide rates in Brazil remained high during the studied period, with differences in trends between regions. Among the potentially associated factors, it was observed that male homicide rate, the high percentage of violent deaths among black women and those with low levels of education, in addition to the low Gross Domestic Product (GDP) per capita, were positively associated with female homicide, whereas larger cities were negatively associated. Interpretation: These findings show that Brazil is a country with a high risk of female homicide. Nevertheless, the vulnerability of women is unequally distributed in the country. Female homicides are mostly caused by domestic conflicts but can also be influenced by changes in the urban and social contexts. Funding: This project is funded by the Bill & Melinda Gates Foundation.